Przewrót Machiavellego - Kimla, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article features a short recapitulation of intellectual achievements in the sphere of politics of Niccolò Machiavelli. On many points he broke with the established way of thinking about politics and steered it in new directions. His revolution was expressed, among other things, in the positioning of politics as a central human activity, in the development of a new methodology for penetrating political matter, in the development of a new perspective on the tasks of political power and on relations between states, in the re-drawing of the relationship between morality and politics, and in an innovative view of the nature of man.
Keywords: Machiavelli, Niccolò (1469-1527); polityka; realizm polityczny; system polityczny; stosunki międzynarodowe; moralność i polityka; wolność obywatelska; natura ludzka; relatywizm; empiryzm; władza polityczna; państwo